Guido Vernani, Averroism, and the Modernity of Dante’s Political Thought - Pérez Carrasco, Mariano (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
The paper presents a reconstruction of the metaphysical core of Dante’s political thought as expressed in the Monarchy, following on the footsteps of Guido Vernani’s critique of Dante’s political ideas in his De reprobatione Monarchie composite a Dante (Bologna, 1327-1334). The paper focuses on the link between Dante’s alleged Averroism, an accusation formulated for the first time by the Dominican friar, but latter repeated by philosophical historiography, and the interpretation of the Monarchy as a sign of the beginning of modern philosophy.
Keywords: Dante Aligheri; Monarchia; Guido Vernani; Averroism; modernity